Linear and non-linear dielectric properties of DTGS in porous Al2O3 films. (26th April 2019) - Stukova, E.; Baryshnikov, S.; Baryshnikova, T.; Solnyshkin, A.
Abstract: The temperature dependences of the dielectric properties and third harmonic coefficient γ3ω of composite materials obtained by embedding DTGS into porous Al2 O3 matrixes with pore diameters of 300 and 100 nm were studied. It is found that the phase transition is diffused and the Curie temperature shifts to low temperatures.